Business and Industry Perceptions of the Soft Skills of Industrial Internship Participants from Vocational High School - Sutendi, Ganjar (Dinasti International Journal of Management Science, 2026)
This study aims to determine the Perceptions of the Business and Industry World regarding the Soft Skills of Industrial Internship Participants from Vocational High Schools (SMK). The obtained perceptions will provide a picture of the readiness of prospective vocational education graduates to face the demands of the workforce. This study apply a descriptive qualitative approach, following with data collection techniques by interviews and supporting documents. The results indicate that, in general, the industry's perspective on the soft skills of Industrial Internship participants is positive, particularly in aspects of discipline, teamwork, responsibility, etiquette, work ethic, and enthusiasm and motivation. However, there are still aspects that need to be developed, such as initiative, communication confidence, and the ability to adapt to digital work systems. Industrial Internship activities play a crucial role in providing experience and providing an overview of students' soft skills. Formal educational institutions should pay more attention to these aspects that need to be developed so that graduates are better prepared for the workforce.